Answer:
Therefore x = 1 is an extraneous solution.
Explanation:
The solution to the equation StartFraction 1 Over x minus 1 EndFraction = StartFraction x minus 2 Over 2 x squared minus 2 EndFraction
![\Rightarrow (1)/(x - 1) = (x- 2)/(2x^2-2) \hspace{0.3cm} \Rightarrow \hspace{0.3cm} 2x^2 - 2 = (x-1)(x-2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/sy7eqfoy9xnvofvqfejoj63ok15hytz577.png)
therefore
![2x^2 - 2 = x^2 - 3x + 2 \hspace{0.3cm} \Rightarrow \hspace{0.3cm} x^2 + 3x - 4 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vxqx9joty83nyjsft6dowc8gwfmy6e61a6.png)
therefore
![x^2 + 3x - 4 = 0 \hspace{0.3cm} \Rightarrow = \hspace{0.3cm} (x-1)(x+4) = 0 \\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6f0b6skogbaaplj2ugwkbna8bajjzw24nl.png)
therefore x = 1 and x = -4 but we can see that if we place x = 1 in the original solution then
which is indeterminate.
Therefore x = 1 is an extraneous solution.